2021
DOI: 10.32014/2021.2518-1491.8
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining Biochar From Rice Husk and Straw

Abstract: This paper presents the results of research on obtaining biochar from agricultural plant waste such as rice husk and straw. The selection of the optimal conditions for thermolysis, such as the duration and temperature of the process, has been conducted. The thermolysis products are characterized for iodine adsorption activity, cumulative water pore volume, and for bulk density. The porous structure of the obtained products has been studied by scanning electron microscopy. Based on the results of the research c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Additionally, a study found that when applied, 30% of the biochar escaped into the atmosphere [164]. The dust produced by the ashes of rice husks has been linked to silicosis, a lung condition that often proves fatal and has irreversible and increasing effects [195].…”
Section: Challenges and Opportunities For Biochar Implementation In A...mentioning
confidence: 99%
“…Additionally, a study found that when applied, 30% of the biochar escaped into the atmosphere [164]. The dust produced by the ashes of rice husks has been linked to silicosis, a lung condition that often proves fatal and has irreversible and increasing effects [195].…”
Section: Challenges and Opportunities For Biochar Implementation In A...mentioning
confidence: 99%
“…In our previous studies, activated carbon was extracted from rice straw and husks, as well as from rice husks and oil sludge [37,38], and binders were used to improve its sorption properties and improve our study. As noted above as a binder lignosulfonate used because it is available and has a high surface activity.…”
Section: Introductionmentioning
confidence: 99%